Effect Adding of Sodium Bicarbonate in Broiler Water On Performance and Immune Response - Jaafar Abdullah, Boraq; Abd Ali Hamza, Mohammed; Hamid Rasool, Majid (Journal of Neonatal Surgery, 2025)
This experiment was carried out in the Poultry Farm in the holy city of Kerbala and use 50 one day old chicks, from 1/2/2018 to 8/3/2018. They were arbitrarily allocated into two experimental groups. Each group consists of 25 chicks. Where sodium bicarbonate was added in drinking water to the treatment group and the other group was considered a control group. Results (1-6 weeks) showed a substantial elevation (P <0.05) in body mass, weight increment, feed intake, and feed efficiency ratio, as well as antibodies titer against Newcastle Disease and Infantile Bursal Disease. Compared to control group. Therefore, sodium bicarbonate is very useful for the economic production of poultry.